Law applicable problems in the frame of international agency agreements: comments about the judgement issued by the Audiencia Provincial de Barcelona on 3 July 2019 - Aguilar Grieder, Hilda (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This study analyses a law applicable problem which arises in the frame of some international agency agreements.
Keywords: European Union; Private International Law; Law applicable; international agency agreements